Encapsulation-induced emission enhancement (EIEE) of Eu(iii)-complexes by aromatic micelles in water. Issue 8 (10th January 2018) - Kai, Tomokuni; Kishimoto, Mai; Akita, Munetaka; Yoshizawa, Michito
Abstract : Typical Eu(iii )-complexes are readily encapsulated in the hydrophobic cavities of aromatic micelles and the resultant host–guest composites exhibit relatively strong red emission (up to Φ = ∼50%) even in water. Abstract : Eu(iii )-complexes emit highly pure and intense red luminescence in aprotic organic solvents, yet the emission is usually quenched completely in the presence of aqueous solvents. Here we report that typical Eu(iii )-complexes are readily encapsulated in the hydrophobic cavities of aromatic micelles, composed of amphiphilic molecules with bent aromatic frameworks. Whereas the emissivity of the Eu(iii )-complexes themselves is zero in aqueous solutions, the resultant host–guest nanocomposites exhibit relatively strong red emission (up to Φ = 48%) with long emission lifetimes (up to τ = 1.05 ms) even in water. Thus, encapsulation-induced emission enhancement (EIEE) of the otherwise water-deactivated luminescent compounds is demonstrated by the aromatic micelle.